Distinctive, fine-scale distribution of Eastern Caribbean sperm whale vocal clans reflects island fidelity rather than environmental variables ... - Vachon, Felicia; Eguiguren, Ana; Rendell, Luke; Gero, Shane; Whitehead, Hal (Dryad, 2022)
Environmental variables are often the primary drivers of species’ distributions as they define their niche. However, individuals, or groups of individuals, may sometimes adopt a limited range within this larger suitable habitat as a result of social and cultural processes. This is the case for Eastern Caribbean sperm whales. While environmental variables are reasonably successful in describing the general distribution of sperm whales in the region, individuals from different cultural groups have distinct distributions around the Lesser Antilles islands. Using data collected over two years of dedicated surveys in the Eastern Caribbean, we conducted habitat modelling and habitat suitability analyses to investigate the mechanisms responsible for such fine-scale distribution patterns. Vocal clan-specific models were dramatically more successful at predicting distribution than general species models, showing how a failure to incorporate social factors can impede accurate predictions. Habitat variation between ... : See the full article for detailed methods. R code based on code from Pirotta et al. 2011 (Modelling sperm whale habitat preference: a novel approach combining transect and follow data) and Eguiguren et al. 2019 (Habitat use of culturally distinct Galápagos sperm whale Physeter macrocephalus clans). ...